Attitude of Farmers towards Mixed Farming - Onima, V. T.; Chauhan, N. B.; Gulkari, Krunal D. (Indian Journal of Extension Education, 2017)
The mixed farming through combination of crop production and their complementary livestock enterprises certainly  create great potential of farms, establishing a complementary relationship between crop and livestock enterprises. To  develop agriculture as a whole, economic condition of farmers is one of the important issues to analyze in popularizing use  of mixed farming for agricultural development; there is a need to understand existing perception of the farmers towards  relevance of mixed farming. As attitude assist individuals in processing complex information and to make decisions, an  instrument has been developed to measure attitude of farmers towards mixed farming, for which “Scale Product Method”  which combines the Thurston's Equal Appearing Interval Scale (1928) for selection of the items and Likert's Summated  Rating Scale (1932) for ascertaining the response on the scale, was followed. The study was conducted on a random  sample of 50 mixed farming adopters selected from ten villages of Anand taluka, of Anand district. It was observed that  majority (90.00 %) of the farmers had positive attitude towards mixed farming. The positivism towards mixed farming  was observed uniformly amongst the farmers with irrespective level of their age, education, farming experience, farm  size, herd size, social participation, mass media exposure, extension contact, economic motivation and achievement  orientation, while it was observed highly positive amongst the farmers with high level of scientific orientation.
Keywords: Attitude; Mixed Farming; Farmers; Adopters; Anand